Community Engagement and Cognition in a Sample of Older Adults Residing in Costa Rica. (30th August 2019) - Valdivieso Mora, E; Ivanisevic, M; Johnson, D
Abstract: Objective: Costa Rica has the highest percentage of older adults (65+) of the Central American and Latin American region. In fact, Costa Rica has the highest life expectancy within an advanced healthcare system and socioeconomic infrastructure that differentiates it from neighboring countries in Central America. Previous research has shown that older adults who engage in higher social engagement show overall better cognitive functioning (Chen et al., 2018); however, limited research has examined the impact of socialization on cognition across rural and urban regions and furthermore no research to date has examined these factors in Costa Rican older adults. This study examined the effects of community engagement on cognition in urban and rural older adults residing in Costa Rica. Participants and Method: Participants were neurotypical older adults residing in San Jose (urban region, n = 156) and Guanacaste (rural region, n = 69). Those with a history of neurological conditions and major psychiatric disorders were excluded. Results: Older adults residing in an urban area (M = 55.43, SD = 23.26) participate more in social engagement within the community compared to those residing in the rural region (M = 46.30, SD = 28.50), p = 0.019. Furthermore, in the urban sample, those with higher social engagement showed better performance on learning and encoding (r = 30), verbal memory (r = 0.26), and executive functioning (r = .20). In older adults residing in the rural region, higher social engagement was only associated with better visuospatial abilities (r = 0.27). Conclusions: Findings suggest that social engagement in the community for older adults in Costa Rica may serve as a protective factor for their cognitive health. However, there are significant differences on what cognitive processes serve as a protective factor as a function of location (rural versus urban). This study highlights the importance of examining the quality of social engagement when evaluating the cognition of Costa Rican older adults. References: Chen, Ya-Mei, Tu, Yu-Kang, Yu, Hsiao-Wei, Chiu, Tzu-Ying, Chiang, Tung-Liang, Chen, Duan-Rung, & Chang, Ray-E. (2018). Leisure time activities as mediating variables in functional disability progression: An application of parallel latent growth curve modeling. PLoS ONE, 13 (10).